2018
DOI: 10.1002/pola.29086
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Polypropylene Surfaces Prepared with TiO2 Nanoparticles Functionalized by Dendritic Polymers

Abstract: Hybrid inorganic–organic nanomaterials have received increasing interest due to the possibility of implementing different functions and characteristics within a single material. Their functionalities are a consequence of the synergy of the properties of distinct building blocks and are related to their varied natures and spatial locations. In this work, we present the development of superhydrophobic properties on polypropylene (PP) surfaces using hybrid nanomateriales from TiO2 nanoparticles (NPs) and dendroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…a new class of materials that exhibit improved performance for the design and control of the properties of polymers and surfaces compared to their microparticle counterparts. [9][10][11][12][13][14] In this context, several research works have shown that the dispersibility, the degree of particle aggregation and the nanoparticle surface chemistry are key parameters for the control of the stability, structure, physical and mechanical properties of nanocomposites, suspensions, foams and mixtures of polymers, maintaining the cohesion between the particles and the host matrix under shearing or thermal constraint. [8,15,16] Among the various inorganic oxides, silica particles have received much attention due to their, high surface area, cost-effective production, and the simple surface modification, biocompatibility and cost-effective production.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…a new class of materials that exhibit improved performance for the design and control of the properties of polymers and surfaces compared to their microparticle counterparts. [9][10][11][12][13][14] In this context, several research works have shown that the dispersibility, the degree of particle aggregation and the nanoparticle surface chemistry are key parameters for the control of the stability, structure, physical and mechanical properties of nanocomposites, suspensions, foams and mixtures of polymers, maintaining the cohesion between the particles and the host matrix under shearing or thermal constraint. [8,15,16] Among the various inorganic oxides, silica particles have received much attention due to their, high surface area, cost-effective production, and the simple surface modification, biocompatibility and cost-effective production.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…I P T remaining inorganic mass, SNP, VNP and ρ correspond to the surface, volume and density of the SiO2 NPs from geometric estimations, NA is the Avogadro's number, Morg is the molecular weight of the incorporated organic group and m0 is initial mass. For the nanoparticle density, ρ, we assumed a value of 1.58 g/cm 3 from literature [12,28,38]. Dynamic light scattering (DLS) DLS measurement was performed in a BI-200SM Goniometer Ver.…”
mentioning
confidence: 99%
“…Where morg is the final mass difference, minorg is the remaining inorganic mass, SNP, VNP and ρ correspond to the surface, volume and density of the SiO2 NPs from geometric estimations, NA is the Avogadro's number, Morg is the molecular weight of the incorporated organic group literature was assumed. [53][54][55] 2.5.4 UV-Vis measurements…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…[ 1,2 ] Those two articles, now reaching nearly 7,000 citations together, open the way for multiple practical applications, such as self‐cleaning, [ 3,4 ] anticorrosion, [ 5–7 ] anti‐icing, [ 8–10 ] low drag resistance, [ 11 ] antimicrobial and antiadhesive, [ 12–14 ] oil–water separation, [ 15,16 ] microelectronic, [ 17 ] among many others. The fabrication of those hierarchical surfaces involves many different techniques, such as vapor deposition, [ 18,19 ] sol–gel, [ 6,20,21 ] plasma treatments, [ 22,23 ] etching, [ 24–26 ] 3D printing, [ 17 ] polymerization, [ 27–29 ] electrochemical deposition, [ 7,30 ] and spray. [ 25,31,32 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Those two articles, now reaching nearly 7,000 citations together, open the way for multiple practical applications, such as self-cleaning, [3,4] anticorrosion, [5][6][7] anti-icing, [8][9][10] low drag resistance, [11] antimicrobial and antiadhesive, [12][13][14] oil-water separation, [15,16] microelectronic, [17] among many others. The fabrication of those hierarchical surfaces involves many different techniques, such as vapor deposition, [18,19] sol-gel, [6,20,21] plasma treatments, [22,23] etching, [24][25][26] 3D printing, [17] polymerization, [27][28][29] electrochemical deposition, [7,30] and spray. [25,31,32] More recently, the preparation of refined microstructures that possess reentrant textures [32][33][34][35][36][37] has allowed, after chemical functionalization, the fabrication of super-repellent surfaces to high surface tension liquids as well as low ones.…”
Section: Introductionmentioning
confidence: 99%